Regulatory capacity capture: The United Kingdom's online safety regime - Lisa-Maria Neudert (Internet Policy Review, 2023)
Worldwide, governments are increasingly concerned about the spread of online harms and big tech's apparent inability to effectively curb them. While some democracies have swiftly implemented regulatory reforms, others, including the United Kingdom, have encountered challenges in developing regulations aimed at platforms. This research investigates the development of the UK's Online Safety Act (OSA) as a key case to examine government capacity for regulating digital platforms. It explores the dynamics between the UK government and platforms, revealing persistent resource asymmetries that not only challenge the government's capacity to regulate but also significantly impact the development of regulatory policies. Drawing from empirical evidence from 33 in-depth, elite interviews with stakeholders from government, industry, and civil society, and archival review, the paper proposes an original framework of regulatory capacity consisting of four resources: information, treasure, authority, and organised expertise. The study finds: 1) the government lacks fundamental regulatory capacity, impeding the development of effective platform regulation; 2) platforms hold superior resources for countering online safety issues; 3) capacity asymmetries between government and platforms pose sustained risks for regulatory capture. Bringing these findings into context with the OSA, this research contends that the Act empowers the government to effectively utilise platform resources for regulatory purposes. However, the success of the Act hinges on the government's capacity to use its authority and enforce the online safety regime. Moving forward, the capacity-based approach introduced in this research offers a rich, analytical framework to examine how the complex interplay between actors and resources affects emergent regulatory systems, thus guiding the development of more robust regulatory strategies.
Keywords: 300; Platform regulation; Platforms; United Kingdom; Online safety; Regulatory capacity